Analysis of the mathematical literacy skills of high school students in solving PISA questions content change and relationship viewed from self-esteem - Cahyani, Rimma Regita; Khotimah, Rita Pramujiyanti (Universitas Islam Negeri Raden Intan Lampung, 2024)
Mathematical literacy is a person's ability to use mathematical science that includes aspects of understanding, application, reasoning, and communication in everyday life. This study aims to analyze and describe students' mathematical literacy in solving questions about changes in PISA content and the relationship that students' self-esteem checks. This research uses qualitative descriptive research methods. The subjects of the study consisted of three Class IX.2 students at Negeri 3 Secondary School Surakarta. Data collection techniques consisted of PISA self-esteem improvement, content change and relationship tests, and interviews. Data analysis techniques consist of data presentation, data reduction, and conclusions. The results of the study show that students with high self-esteem can meet the six indicators of mathematical literacy in both subjects.